A case report of purulent pericarditis caused by Candida albicans: Delayed complication forty-years after esophageal surgery. Issue 28 (July 2018) - Sung, Joowhan; Perez, Irving Enrique; Feinstein, Addi; Stein, David Kidd
Abstract: Rationale: Candida pericarditis is a rare condition with high mortality. Risk factors include thoracic surgery and immunosuppression. We report a case of candida pericarditis which developed forty-years after esophageal reconstruction surgery. Patient concerns: A 42-year-old female presented with nausea, abdominal discomfort, and chest pain, and was found to have a cardiac tamponade secondary to candida pericarditis. Her notable risk factor was colonic interposition done during her infancy for esophageal atresia. Diagnoses: The patient underwent emergent pericardial window where 500cc of purulent fluid was drained. The pericardial fluid culture grew Candida albicans . Interventions: Esophagram did not show any visible leak and the patient improved with surgical drainage and antifungal treatment with Caspofungin. Caspofungin was continued intravenously for a total of four weeks and was switched to fluconazole. Outcomes: An Echocardiogram performed one month after pericardial window revealed trivial pericardial effusion. Serum beta-D-glucan at the time was negative. Lessons: This report highlights that candida pericarditis infection could occur as a late complication of colonic interposition. We also demonstrate the utility of using an echinocandin in treating this entity.